Pemanfaatan Media Sosial Untuk Memasarkan Penjualan Mie Ayam Dan Bakso Ananda Di Desa Durian Demang - Lesmana, Arif; Astuty, Kamelia; Nurzam, Nurzam; Wagini, Wagini (Jurnal Dehasen Untuk Negeri, 2024)
The Mie Ayam and Bakso Ananda business in Durian Demang Village faces challenges in increasing visibility and sales amid intense competition. This study aims to assist the business by developing and implementing a digital marketing strategy. The method used includes observation, interviews, and surveys to identify marketing needs and opportunities. The strategy implemented involves using social media platforms such as Facebook, Instagram, and WhatsApp to promote products. Training and mentoring were provided to the business owner on how to optimize the use of social media. The results of the activities showed significant increases in the number of customers, social media followers, and product sales. The implementation of the digital marketing strategy proved effective in enhancing the business's visibility and competitiveness. In conclusion, digital marketing strategies can be an effective solution for small and medium-sized enterprises to face market competition. It is recommended that business owners continuously develop their digital marketing skills and collaborate with marketing experts to maintain the achieved success.